Effect of CO2-induced platicization and membrane configuration on the performance of asymmetric polysulfone hollow fiber membrane for CO2/CH4 gas separation - Yaacob, Nurshahnawal (2005)
The present study focuses on the effect of CO2-plasticization and membrane configuration on the performance of asymmetric polysulfone hollow fiber membrane for CO2/CH4 separation. Heat treatment method to suppress plasticization effect and membrane module configurations in series and cascades arrangement for the CO2/CH4 gas separation was investigated. The membranes were prepared using polysulfone (Udel P1700) and tested using pure CO2 and CH4 and CO2/CH4 gas mixture. Gas permeation experiments were conducted for single, two and three-stage configurations. The produced membranes were characterized by pure gas permeation experiments, density measurement, Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM) and Thermogravimetric Analysis (TGA). In pure gas permeation experiment for both untreated and treated membranes, the pressure-normalized flux of CO2 decreases with increasing of the membrane stages. In addition, the selectivities of the asymmetric polysulfone hollow fiber membrane showed a more constant trend with increasing feed pressure. Treated membrane exhibited lower pressure-normalized flux than untreated membranes due to skin layer densification which increases the gas transport resistance which lead to the reduction in the CO2 pressure-normalized flux values. Among all configurations studied, twostage series configuration showed the most constant trend of selectivity values. The selectivity is slightly below the intrinsic selectivity. However, three-stage cascade configuration produced the highest CO2/CH4 selectivity especially when tested at low feed pressure range. Some of the selectivity even surpasses the intrinsic selectivity of polysulfone. Effect of stage cut on feed pressure showed an increasing trend with increasing of CO2 and CH4 feed pressure in all configurations. This is due to the increase of the permeation driving force, which causes the passage of larger amounts of more permeable gas through the membrane. This study showed that, three-stage cascade configuration exhibited the smallest stage cut values than other module configurations. Hence, cascade configuration produces higher purity of CO2 in the permeate stream. In mixed gas permeation experiment, increasing trend of CO2 pressure-normalized flux was also observed but exhibited lower value due to competition among the penetrant species. As a result, the selectivity and the stage cut achieved are also lower in values. As a conclusion, the results of this work served as a platform in determining the most suitable module configuration to be used for gas separation processes.